Finite element analyses on hysteretic behavior of steel frames infilled with AAC masonry wall with circular-arc openings - Yu, You-Sheng; Li, Cheng; Cui, Yu-Min; Guo, Ya-Nan (Journal of Asian architecture and building engineering, 2023)
The steel frame infilled with the autoclaved lightweight aerated concrete (AAC) masonry wall is widely applied in buildings. However, earthquake damage investigation has revealed that infill walls have a significant influence on the mechanical behaviors of the frame structure. In this paper, a new type of AAC masonry wall with circular-arc openings at the corners was proposed based on the principle that setting openings at the corners of the infill wall would weaken the tension (compression) band, so as to reduce the unfavorable interaction between the steel frame and the infill walls. Additionally, the seismic performance of steel frames infilled with AAC masonry walls with circular-arc openings at the corners under low cycle loading was investigated through finite element (FE) method simulations on 11 specimens. The results demonstrated that the circular-arc openings are effective in delaying the cracking of the AAC wall and weakening the additional stiffness of the AAC masonry wall for the steel frame.